The Boxcar Children : The Zombie Project - Book 128 - Warner, Gertrude Chandler 1890-1979.; Papp, Robert (Chicago : Albert Whitman, 2011)
While staying at the Winding River Lodge, the Alden siblings investigate tales of a zombie haunting a lake in the woods.
Keywords: Siblings -- Fiction; Orphans -- Fiction; Zombies -- Fiction; Fiction